2022
DOI: 10.1200/jco.21.01252
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Model of Severe Fatigue After Breast Cancer Diagnosis: Toward a Personalized Framework in Survivorship Care

Abstract: PURPOSE Fatigue is common and troublesome among breast cancer survivors; however, limited tools exist to predict its risk. PATIENTS AND METHODS Participants with stage I-III breast cancer were prospectively included from CANTO (ClinicalTrials.gov identifier: NCT01993498 ), collecting longitudinal data at diagnosis (before the initiation of any cancer treatment) and 1 (T1), 2 (T2), and 4 (T3) years after diagnosis. The main outcome was severe global fatigue at T2 (score ≥ 40/100, European Organisation for Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…81,82 In the context of recently consolidated strategies of endocrine therapy escalation, [83][84][85] particular attention should be given to specific subgroups, such as younger women, who seem to be at higher risk of QOL deterioration and persistent symptoms. 86 The strengths of this study include its prospective, longitudinal design, and a large and heterogeneous sample. We analyzed a single, higher-order QOL outcome measure that summarizes multiple scales into a multidimensional response profile, thus avoiding multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 In the context of recently consolidated strategies of endocrine therapy escalation, [83][84][85] particular attention should be given to specific subgroups, such as younger women, who seem to be at higher risk of QOL deterioration and persistent symptoms. 86 The strengths of this study include its prospective, longitudinal design, and a large and heterogeneous sample. We analyzed a single, higher-order QOL outcome measure that summarizes multiple scales into a multidimensional response profile, thus avoiding multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“… 81 , 82 In the context of recently consolidated strategies of endocrine therapy escalation, 83 - 85 particular attention should be given to specific subgroups, such as younger women, who seem to be at higher risk of QOL deterioration and persistent symptoms. 86 …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested that the patient population that is at higher risk of cancer-related fatigue includes (1) those who are more fragile at the time of diagnosis, including being young, belonging to lower socioeconomic class, not partnered, having higher BMI, comorbidities, being a smoker, presenting heavier psychologic distress (depressive and anxiety symptoms), and concomitant symptom burden and (2) those who receive specific classes of treatment such as chemotherapy and endocrine therapy. [4][5][6][7][8][9]26 Some previous studies have suggested that there are clusters of patients who experience distinct trajectories of fatigue. 27 For example, Bower et al examined post-treatment fatigue trajectories in 191 women with early-stage BC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the currently ongoing CANTO longitudinal cohort has led to the validation of a predictive model of severe fatigue; severe fatigue was defined as a fatigue score ≥40% according to the European Organisation for Research and Treatment of Cancer quality-of-life core questionnaire with 30 items (EORTC QLQ-C30). In this model, retained risk factors for severe fatigue at 2 years after diagnosis were pretreatment fatigue, younger age, higher body mass index, current smoking behavior, worse anxiety, insomnia, and pain at diagnosis; hormonal treatment was found to be a risk factor for severe fatigue 4 years after diagnosis [25].…”
Section: Fatigue During Breast Cancer Treatmentmentioning
confidence: 99%